Field investigation on the influence of periglacial processes on pile foundations on the Qinghai–Tibet plateau. (1st December 2020) - Guo, Lei; You, Yanhui; Yu, Qihao; Shi, Zhaoyun; Li, Hongbi; Wang, Xinbin
Abstract: Periglacial processes can threaten the operation of engineering infrastructure. Based on field observations, the influence of four types of periglacial processes on tower foundations along the Qinghai–Tibet Engineering Corridor were investigated. These periglacial processes change the local thermal and hydraulic processes in soils around the pile foundations, thereby threatening their stability. Frost heaving‐related periglacial phenomena and fast mass wasting are major threats for the operation of pile foundations. The long‐term stability of pile foundations is also threatened by thermokarst‐related periglacial processes and slow mass wasting under the evolving climate change scenario on the Qinghai–Tibet Plateau. Frost weathering has a slight impact on the stability of concrete pile heads, and the long‐term effects of this cannot be ignored. In addition to the impacts of periglacial processes, piles are also affected by engineering problems in areas with shallow artesian ground water, where the use of thermosyphons is associated with frost jacking of the foundations. Further studies are needed on the thermal and hydraulic regimes in soils under the influence of artesian ground water and thermokarst lakes/ponds.